Influence of Heterogeneity on the Ultrafast Photoisomerization Dynamics of Pfr in Cph1 Phytochrome1. (13th May 2017) - Stensitzki, Till; Yang, Yang; Wölke, Anna Lena; Knapp, Ernst‐Walter; Hughes, Jon; Mroginski, Maria Andrea; Heyne, Karsten
Abstract: Photoisomerization of a protein‐bound chromophore is the basis of light sensing and signaling in many photoreceptors. Phytochrome photoreceptors can be photoconverted reversibly between the Pr and Pfr states through photoisomerization of the methine bridge between rings C and D. Ground‐state heterogeneity of the chromophore has been reported for both Pr and Pfr. Here, we report ultrafast visible (Vis) pump–probe and femtosecond polarization‐resolved Vis pump–infrared (IR) probe studies of the Pfr photoreaction in native and 13 C/ 15 N‐labeled Cph1 phytochrome with unlabeled PCB chromophore, demonstrating different S0 substates, Pfr‐I and Pfr‐II, with distinct IR absorptions, orientations and dynamics of the carbonyl vibration of ring D. We derived time constants of 0.24 ps, 0.7 ps and 6 ps, describing the complete initial photoreaction. We identified an isomerizing pathway with 0.7 ps for Pfr‐I, and silent dynamics with 6 ps for Pfr‐II. We discuss different origins of the Pfr substates, and favor different facial orientations of ring D. The model provides a quantum yield for Pfr‐I of 38%, in line with ~35% ring D rotation in the electronic excited state. We tentatively assign the silent form Pfr‐II to a dark‐adapted state that can convert to Pfr‐I upon light absorption. Abstract : Photoisomerization of a protein‐bound chromophore is the basis of light sensing and signaling in many photoreceptors. Femtosecond polarization‐resolved VIS pump–IR probe spectroscopy reveals heterogeneity in the Pfr ground state of Cph1 phytochrome with distinct dynamics and quantum yields. We identified an isomerizing pathway with 0.7 ps for Pfr‐I, and silent dynamics with 6 ps for Pfr‐II. In combination with quantum chemistry calculations, we propose two different conformations that differ in ring D orientation and in distances to D207 and Y263, resulting in distinct hydrogen bond strengths. Hence, small changes in the protein–chromophore interaction can switch the photoreaction outcome.